Thermal Pulse Studies of Integrated Piezoceramics. Issue 12 (20th August 2018) - Eydam, Agnes; Suchaneck, Gunnar; Gerlach, Gerald
Abstract : Integrated piezoceramics enable smart structures which interact with their environment. Their polarization state can be probed by thermal methods based on the pyroelectric effect. In this work, single PZT plates and PZT plates embedded into low temperature co‐fired ceramics (LTCC) are heated by thermal pulses and the pyroelectric current is measured in time domain. Analytical and numerical models to describe the mean temperature of the sample and derive the pyroelectric current are presented by the authors. Single‐layer and two‐layer models are used and the effects of a finite pulse width, the electrode, and heat losses are investigated. The goal is to find a suitable model characterizing the pyroelectric current in time domain as basis to derive information on the corresponding polarization state. Abstract : The polarization state of integrated piezoceramics is evaluated by the thermal pulse method. PZT samples are heated by thermal pulses and the pyroelectric current is measured in time domain. Analytical and numerical models describe the temperature distribution and the pyroelectric current is derived and compared to experimental results.